Microstructural Characterization and Mechanical Properties of Ti-6Al-4V Alloy Subjected to Dynamic Plastic Deformation Achieved by Multipass Hammer Forging with Different Forging Temperatures. (27th August 2019) - Fang, Xiurong; Wu, Jiang; Ou, Xue; Yang, Fuqiang
Abstract : Dynamic plastic deformation (DPD) achieved by multipass hammer forging is one of the most important metal forming operations to create the excellent materials properties. By using the integrated approaches of optical microscope and scanning electron microscope, the forging temperature effects on the multipass hammer forging process and the forged properties of Ti-6Al-4V alloy were evaluated and the forging samples were controlled with a total height reduction of 50% by multipass strikes from 925°C to 1025°C. The results indicate that the forging temperature has a significant effect on morphology and the volume fraction of primary α phase, and the microstructural homogeneity is enhanced after multipass hammer forging. The alloy slip possibility and strain rates could be improved by multipass strikes, but the marginal efficiency decreases with the increased forging temperature. Besides, a forging process with an initial forging temperature a bit above β transformation and finishing the forging a little below the β transformation is suggested to balance the forging deformation resistance and forged mechanical properties.